Adaptive monitoring: a new paradigm for long-term research and monitor ing - Lindenmayer, David B.; Likens, Gene E. (Trends in Ecology & Evolution, 2009)
Long-term research and monitoring can provide important ecological ins ights and are crucial for the improved management of ecosystems and na tural resources. However, many long-term research and monitoring progr ams are either ineffective or fail completely owing to poor planning a nd/or lack of focus. Here we propose the paradigm of adaptive monitori ng, which aims to resolve many of the problems that have undermined pr evious attempts to establish long-term research and monitoring. This p aradigm is driven by tractable questions, rigorous statistical design at the outset, a conceptual model of the ecosystem or other entity bei ng examined and a human need to know about ecosystem change. An adapti ve monitoring framework enables monitoring programs to evolve iterativ ely as new information emerges and research questions change.